Visualizing lithium ions in the crystal structure of Li3PO4 by in situ neutron diffraction - Manawan, Maykel; Kartini, Evvy; Avdeev, Maxim (Journal of applied crystallography, 2021)
Li3PO4 is known to demonstrate Li+ ionic conductivity, making it a good candidate for solid electrolytes in all‐solid batteries. Understanding the crystal structure and its connection to Li+ diffusion is essential for further rational doping to improve the ionic transport mechanism. The purpose of this study is to investigate this mechanism using anisotropic displacement parameters (ADPs), nuclear density distribution and bond valence mapping. In situ neutron powder diffraction experiments have been performed using the high‐resolution powder diffractometer ECHIDNA at the OPAL reactor, Australian Centre for Neutron Scattering, Australian Nuclear Science and Technology Organisation, NSW, Australia. The ADPs and nuclear density distribution were determined from the analysis of neutron diffraction data using the Rietveld method, whereas the bond valence map was calculated from the refined structure. The crystal structure remained unchanged as the temperature was increased (3, 100, 300 and 400 K). However, the ADPs show a greater increase in anisotropy in the a and b axes compared with the c axis, indicating the tendency of the ionic movement. By combining nuclear density distribution and bond valence mapping, the most likely lithium‐ion diffusion in the crystal structure can be visualized. The structure dynamics in Li3PO4 crystals are investigated using temperature‐dependent neutron powder diffraction, which shows that the anisotropic displacement parameters, nuclear density distribution and bond valence map are subject to change with temperature. This information is useful for the study of lithium‐ion diffusion in the crystal structure of a cathode or solid electrolyte for lithium‐ion batteries.